Governance for regenerative coordination: the evolution from DAO to DAO 3.0 - Bennett, Kate (Frontiers in Blockchain, 2025)
IntroductionDecentralized Autonomous Organizations (DAOs), digital organizations governed by code and community, offer new paradigms for collective governance; yet many early examples have reproduced the power asymmetries, exclusionary participation models, and inefficiencies found in traditional systems. This study examines how DAO governance can evolve to support fair, inclusive, and regenerative capital flows across distributed ecosystems, particularly in contexts where traditional coordination infrastructure is limited.MethodsA qualitative case study was conducted on Hypha, an organisation that evolved from a classic DAO to a Decentralized Human Organization (DHO) and subsequently to an Adaptable Organization, or DAO 3.0. Data was collected through semi-structured interviews and document analysis, then interpreted using a People–Process–Technology framework to identify governance design principles. This was supported by a comparative taxonomy mapping the evolution from DAO 1.0 to DAO 3.0.ResultsFindings show a progression from early token-weighted DAO 1.0 models, through protocol-optimized DAO 2.0 structures, to DAO 3.0’s modular, relational, and context-adaptive designs. Hypha’s governance innovations include multi-layer modular voting, “leadership without control” protocols, real-time capital flow mechanisms, and trust-based safeguards that address fairness failures, enhance adaptability, and enable governance to respond dynamically to human complexity and local contexts.DiscussionThe Hypha case study positions DAO 3.0 as a prototype for regenerative coordination infrastructure where governance operates as a living system, balancing technological automation with human-centered design. This research expands DAO governance theory by clarifying conceptual boundaries, integrating recent literature, and providing practical guidance for policymakers, developers, and capital providers seeking to design equitable, regenerative governance and coordination systems.